The factors relate with occurrence of cronic energy deficiency to pregnant woman in the working area of puskesmas mutiara barat, 2023 - Idawati; Rahamani, Lola; Ramadhana, Meiza; Jannati, Rahmi; Murti, Selly (Trigin Institute, 2023)
Chronic Energy Deficiency (CED) of pregnant women can affect the process of fetal growth. Data from the Aceh Health Office (2016), the incidence of SEZ in pregnant women was 10.9%, whereas in Pidie Regency it was 10.3%. This study aimed to determine the factors associated with the incidence of chronic energy deficiency (CED) in pregnant women in UPTD PuskesmasSumanda in 2020. The design used is quantitative with a cross-sectional approach. A total of 164 samples of pregnant pregnant women in the working area of the Mutiara Barat Health Center.Sampling technique with accidental sampling. Data collection using a questionnaire on the sample. The analysis used in this study is univariate with frequency distribution, bivariate with chi square. The results showed that 37.2% of pregnant women experienced KEK. Rp 3,410,000) (62.8%) Statistical test results have a relationship between age and the incidence of chronic energy deficiency (p value = 0,000). There is a relationship between parity and the incidence of chronic energy deficiency in pregnant women (p value = 0,000). There is a relationship between the level of income with the incidence of chronic energy shortages in pregnant women (p value = 0,000). Based on this, an approach is needed from health. workers to provide counseling about age, parity, and socioeconomic related to CED in pregnant women.